PENGARUH SOSIALISASI PERPAJAKAN DAN PENGETAHUAN PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK MELALUI KESADARAN WAJIB PAJAK SEBAGAI VARIABEL INTERVENING (Studi pada Pelaku UMKM yang Terdaftar di KPP Pratama Semarang Timur) - Intan Karunia Sari; Saryadi Saryadi (Jurnal Ilmu Administrasi Bisnis, 2019)
This study aims to determine the effect of tax socialization and tax knowledge partially on taxpayer compliance through taxpayer awareness. The type of research used is explanatory research. Sampling uses the multy stage sampling method, with 96 respondents being taxpayers of micro, small and medium enterprises (MSMEs) registered at the KPP Pratama Semarang Timur. The data used are secondary data from the report on tax receipts and the level of taxpayer compliance for the period 2014-2017, besides that with primary data from the respondents' direct answers in the form of processed questionnaires. This study uses descriptive analysis, validity test, reliability test, correlation coefficient, coefficient of determination, regression analysis, t test, F test, with the help of SPSS version 23 data processing and sobel test to analyze the effect of mediating variables. The results showed that tax socialization and taxation knowledge partially had a positive and significant effect on taxpayer awareness. Partially socialization of tax, knowledge of tax, awareness of taxpayers has a positive and significant effect on taxpayer compliance. As an intervening variable the awareness of taxpayers can’ be a mediation between tax socialization and tax knowledge partially towards taxpayer compliance.